Answer

Verified

374.7k+ views

**Hint:**Here, we are given the first term and the common difference of an arithmetic sequence. Therefore, we need to use the formula for finding the $nth$term of the arithmetic sequence. By this formula and the given information, we can obtain a linear equation with variable $n$in which we can obtain the terms by putting the value of $n$.

**Formula used:**${a_n} = {a_1} + \left( {n - 1} \right)d$, where, ${a_n}$is the $nth$ term of the arithmetic sequence, ${a_1}$ is the first term of the arithmetic sequence and $d$is the common difference between two consecutive terms in the arithmetic sequence

**Complete step-by-step solution:**

We know that for the arithmetic sequence,

${a_n} = {a_1} + \left( {n - 1} \right)d$

We are given that the first term ${a_1} = - 4$and the common difference $d = 10$.

$

\Rightarrow {a_n} = - 4 + \left( {n - 1} \right)10 \\

\Rightarrow {a_n} = - 4 + 10n - 10 \\

\Rightarrow {a_n} = 10n - 14 \\

$

We are asked to find the first six terms of the arithmetic sequence.

The first term is already given to us which is ${a_1} = - 4$.

We can find the second term by putting the value of $n = 2$ in the equation ${a_n} = 10n - 14$.

$ \Rightarrow {a_2} = 10\left( 2 \right) - 14 = 20 - 14 = 6$

We can find the second term by putting the value of $n = 3$ in the equation ${a_n} = 10n - 14$.

$ \Rightarrow {a_3} = 10\left( 3 \right) - 14 = 30 - 14 = 16$

We can find the second term by putting the value of $n = 4$ in the equation ${a_n} = 10n - 14$.

$ \Rightarrow {a_4} = 10\left( 4 \right) - 14 = 40 - 14 = 26$

We can find the second term by putting the value of $n = 5$ in the equation ${a_n} = 10n - 14$.

$ \Rightarrow {a_5} = 10\left( 5 \right) - 14 = 50 - 14 = 36$

We can find the second term by putting the value of $n = 6$ in the equation ${a_n} = 10n - 14$.

$ \Rightarrow {a_6} = 10\left( 6 \right) - 14 = 60 - 14 = 46$

Thus, the first six terms of the arithmetic sequence are $ - 4,6,16,26,36,46$.

**Note:**In this type of question where the first term and the common difference of an arithmetic sequence is given, we can also obtain the first few terms by simply adding the common difference to the consecutive terms. For example, here the first term is given as $ - 4$. When we simply add the common difference $10$, we get our second term $6$. Thus, by repeating this four more times, we get the first six terms of the arithmetic sequence.

Recently Updated Pages

Cryolite and fluorspar are mixed with Al2O3 during class 11 chemistry CBSE

Select the smallest atom A F B Cl C Br D I class 11 chemistry CBSE

The best reagent to convert pent 3 en 2 ol and pent class 11 chemistry CBSE

Reverse process of sublimation is aFusion bCondensation class 11 chemistry CBSE

The best and latest technique for isolation purification class 11 chemistry CBSE

Hydrochloric acid is a Strong acid b Weak acid c Strong class 11 chemistry CBSE

Trending doubts

Give 10 examples for herbs , shrubs , climbers , creepers

Difference Between Plant Cell and Animal Cell

Name 10 Living and Non living things class 9 biology CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

List some examples of Rabi and Kharif crops class 8 biology CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE